Defining Maritime Cultural Landscapes in California. (3rd July 2019) - Gusick, Amy E.; Dodds, Tricia; Jaffke, Denise; Meniketti, Marco; Ball, David
ABSTRACT: Defining a maritime cultural landscape relies on recognizing both the landscape and seascape as integral to maritime societies. While this concept has been part of anthropological studies for decades, data from the submerged portion of the maritime landscape is often overlooked. The maritime archaeological work needed to collect these data has historically been marginalized within the broader archaeological discipline, but is slowly gaining widespread acceptance. More island and coastal researchers have begun integrating land- and sea-based data into their project designs, promoting recognition of the importance of sea-based data from submerged landscapes and encouraging understanding that maritime cultural landscapes shaped and are shaped by maritime societies. Among the many maritime cultural landscapes worldwide, we present two examples from California that exemplify how researchers are conceptualizing maritime landscapes and gathering data necessary for a holistic view of maritime societies and the spaces that influence their cultural development.